PENGARUH BIAYA OPERASIONAL DENGAN PENDAPATAN OPERASIONAL (BOPO) DAN DANA PIHAK KETIGA TERHADAP RETURN ON ASSET (ROA) PADA BANK PERKREDITAN RAKYAT - Kevin Varianto Jorjoga; Yunika Murdayanti (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
This research was intended to examine the effect of how great the performance of Bank Perkreditan Rakyat, which was measured by ROA during period 2009 to 2012. The independent variables used in this research were operating expense to operating revenue (BOPO) and Third Party Funds. While, its dependent variable was the Return on Asset (ROA) of Bank Perkreditan Rakyat. This research used secondary data that was obtained from the report of BPR in DKI Jakarta, which has been published through Bank Indonesia or Otoritas Jasa Keuangan in 2009 to 2013. The technique that was used to gather the sample was purposive sampling and there were 10 companies obtained with a total sample of 50 companies. The method used in this research was multiple linear regression analysis. The result of t-test showed that the first variable, BOPO, had a negative and significant effect to ROA of Bank Perkreditan Rakyat. The second variable, which was Dana Pihak Ketiga, also showed a negative and significant effect to ROA. Key Words : Return On Asset, operating Expense to Operating Revenue (BOPO), Third Party funds